Examining the ecological validity of the coaching behavior scale (sports) for basketball - Koh, K. T.; Mallett, C.; Wang, C. K. J. (International Journal of Sports Science and Coaching, 2009)
This study examined the key tasks of high-performance basketball coaches in Singapore using the Coach Behavior Scale for Sports (CBS-S). Seventeen participants (national coaches, team managers, players and other experts) took part in the study in which quantitative (CBS-S) and qualitative (semi-structured interviews) data were collected. The quantitative data were analysed using SPSS (Version 15.0) and the qualitative data were content analysed by three experienced researchers in sport psychology and coaching. The dimensions and items from the CBS-S were considered mostly relevant in evaluating the work of Singapore high-performance basketball coaches. However, some modifications were made to the CBS-S to make it more specific to the basketball context in Singapore based on conceptual, theoretical and empirical considerations. The final version of the Singapore CBS-S (Basketball) has 9 dimensions with 96 items as opposed to the original CBS-S with 7 dimensions and 70 items. Overall, the findings from this study were consistent with the literature on coaches' work.